COMPARISON BEST VIDEO CONFERENCE FOR LEARNING AND TEACHING ACTIVITIES USING ANALYTIC HIERARHICAL PROCESS - Januponsa Dio Firizqi; Saiful Azhari Muhammad; Richardus Eko Indrajit; Nurul Hidayat; Erick Dazki (Informatika, Universitas Jenderal Soedirman, 2022)
During the pandemic, almost all industries have been disrupted, including the education industry. To support the sustainability of the education industry, many institutions use various video conferencing platforms. There are six aspects that need to be considered in choosing a video conference platform: Features provided, Ease of use, security level, bandwidth usage, platform stability and the ability to accommodate the number of participants in a conference room. This study shows how to prioritize these aspects in choosing a video conferencing platform carried out by educational institutions in Indonesia. The method used in this research is the Analytical Hierarchical Process (AHP). And the results of this study show the order of aspects in choosing a video conferencing platform for teaching and learning needs.